Adhesive for electronic material and liquid crystal display element

JP2025031618APending Publication Date: 2025-03-07SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024136907
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-24
Filing Date
2024-08-16
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0060】 本発明によれば、描画性及びシリンジ中への壁残り防止性に優れる電子材料用接着剤を提供することができる。また、本発明によれば、該電子材料用接着剤を用いてなる液晶表示素子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031618000001
    Figure 2025031618000001
  • Figure 2025031618000002
    Figure 2025031618000002
Patent Text Reader

Abstract

To provide an adhesive for an electronic material which has an excellent drawing property and an excellent prevention property of preventing remaining in the wall of a syringe, and to provide a liquid crystal display element using the adhesive for an electronic material.SOLUTION: The present invention relates to an adhesive for an electronic material containing a cured resin and an inorganic filler. The viscosity measured at the temperature of 25°C and 0.01 rpm by using an E-type viscosity meter is 1.5 million mPa-s at a maximum. The thixotropic index, which is the value obtained by dividing the viscosity measured at the temperature of 25°C and 0.01 rpm by the viscosity measured at the temperature of 25°C and 1 rpm, is at least 3.0 and is 5.0 at a maximum.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive for electronic materials. The present invention also relates to a liquid crystal display device using the adhesive for electronic materials. [Background technology]

[0002] In recent years, liquid crystal display elements and organic EL display elements have been widely used as display elements characterized by their thinness, light weight, low power consumption, etc. In such display elements and other electronic devices, adhesives for electronic materials are usually used for bonding various members and sealing the liquid crystal and light-emitting layers, etc. For example, in recent years, a liquid crystal dropping method using an adhesive for electronic materials as a sealant, as disclosed in Patent Documents 1 and 2, has been used as a method for manufacturing liquid crystal display elements such as liquid crystal display cells, from the viewpoint of shortening takt time and optimizing the amount of liquid crystal used. In the dropping method, a frame-shaped seal pattern is first formed by dispensing on one of two substrates with electrodes. Next, while the sealant is in an uncured state, minute droplets of liquid crystal are dropped into the seal frame of the substrate, and the other substrate is superimposed under vacuum, and the sealant is cured to produce a liquid crystal display element. Currently, this dropping method is the mainstream method for manufacturing liquid crystal display elements. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-133794 A [Patent Document 2] WO 02 / 092718 Summary of the Invention [Problem to be solved by the invention]

[0004] The electronic material adhesive is usually filled into a dispensing syringe and degassed before it is used continuously. However, if the electronic material adhesive remains on the wall of the syringe, the remaining electronic material adhesive may fall back into the electronic material adhesive in the syringe due to vibration of the device or the like, causing the electronic material adhesive to contain air bubbles. Since the electronic material adhesive containing air bubbles is likely to cause drawing defects such as disconnection, it is required that the electronic material adhesive not remain on the wall of the syringe. As a method for preventing the electronic material adhesive from remaining on the wall of the syringe, it is considered to reduce the viscosity of the electronic material adhesive. However, when the viscosity of the electronic material adhesive is reduced, there are problems such as poor fine line drawing properties and a tendency for the liquid crystal to penetrate into the sealant when the electronic material adhesive is used as a sealant for liquid crystal display elements.

[0005] An object of the present invention is to provide an adhesive for electronic materials that is excellent in drawability and in preventing residue on the wall of a syringe. Another object of the present invention is to provide a liquid crystal display element using the adhesive for electronic materials. [Means for solving the problem]

[0006] Disclosure 1 relates to an adhesive for electronic materials that contains a curable resin and an inorganic filler, and that has a viscosity of 1.5 million mPa s or less when measured using an E-type viscometer at 25°C and 0.01 rpm, and a thixotropic index, which is the value obtained by dividing the viscosity measured using an E-type viscometer at 25°C and 0.01 rpm by the viscosity measured at 25°C and 1 rpm, of 3.0 or more and 5.0 or less. Disclosure 2 is the adhesive for electronic materials of Disclosure 1, in which the content of the inorganic filler is 30 parts by mass or more per 100 parts by mass of the curable resin. In the present disclosure 3, the inorganic filler includes an inorganic filler that has been surface-treated with a surface treatment agent, and the surface treatment agent has a polarity term δp of the Hansen solubility parameter of 3.5 MPa. 0.5 More than 6.0MPa 0.5 The adhesive for electronic materials according to Disclosure 1 or 2 is as follows. Disclosure 4 is the adhesive for electronic materials of Disclosure 1, 2, or 3, wherein the inorganic filler has a particle size D50, at which the cumulative mass from the smallest particle size side in the particle size distribution accounts for 50%, of 300 nm or more. Disclosure 5 is the adhesive for electronic materials of Disclosure 1, 2, 3, or 4, wherein the inorganic filler has a particle size distribution in which a particle size D50, at which the cumulative mass from the minimum particle size side is 50%, is 2 μm or less, and a particle size D100, at which the cumulative mass from the minimum particle size side is 100%, is 6 μm or less. The present disclosure 6 is an adhesive for electronic materials according to the present disclosure 1, 2, 3, 4, or 5, which does not contain an organic filler having a particle size D50 of 50 nm or more and 500 nm or less, where the cumulative mass from the smallest particle size side in the particle size distribution is 50%, or the content of an organic filler having D50 of 50 nm or more and 500 nm or less is 10 parts by mass or less per 100 parts by mass of the curable resin. The present disclosure 7 is a liquid crystal display device comprising a cured product of the adhesive for electronic materials according to the present disclosure 1, 2, 3, 4, 5 or 6. The present invention will be described in detail below.

[0007] The present inventors have investigated how to adjust the thixotropic index of an electronic material adhesive containing a curable resin and an inorganic filler to a specific range while adjusting the viscosity measured at a low rotation speed using an E-type viscometer to a specific value or more, and have found that it is possible to obtain an electronic material adhesive that is excellent in drawability and in preventing residue on the wall of a syringe, thereby completing the present invention.

[0008] The adhesive for electronic materials of the present invention has an upper limit of viscosity of 1.5 million mPa s, measured using an E-type viscometer at 25°C and 0.01 rpm. By having the above viscosity of 1.5 million mPa s or less, the adhesive for electronic materials of the present invention has excellent resistance to remaining on the wall of a syringe. The preferred upper limit of the viscosity is 1.3 million mPa s, and the more preferred upper limit is 1.1 million mPa s. From the viewpoint of drawability and the like, the lower limit of the above viscosity is preferably 600,000 mPa·s, and more preferably 800,000 mPa·s. As the E-type viscometer, for example, DV-III (manufactured by BROOK FIELD) can be used.

[0009] The adhesive for electronic materials of the present invention has a thixotropic index (hereinafter also referred to as "Ti value") of 3.0 at the lower limit and 5.0 at the upper limit, which is the value obtained by dividing the viscosity measured at 25°C and 0.01 rpm using an E-type viscometer by the viscosity measured at 25°C and 1 rpm. When the Ti value is within this range, the adhesive for electronic materials of the present invention has excellent drawability. When the Ti value is within this range, the adhesive for electronic materials of the present invention is also excellent in the effect of preventing liquid crystal from being inserted when used as a sealant for liquid crystal display elements. The lower limit of the Ti value is preferably 3.2, and the upper limit is preferably 4.8, and more preferably 3.4, and more preferably 4.6.

[0010] Examples of methods for adjusting the viscosity and Ti value within the above ranges include a method of adjusting the type and content of each component, such as a curable resin and an inorganic filler, which will be described later.

[0011] The adhesive for electronic materials of the present invention contains an inorganic filler. The inorganic filler has roles in the adhesive for electronic materials, such as adjusting the viscosity, improving the adhesiveness, improving the linear expansion coefficient, and improving the moisture permeability prevention properties of the cured product.

[0012] Examples of the inorganic filler include silica, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, alumina, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, calcium silicate, etc. Among these, silica is preferable.

[0013] The inorganic filler preferably includes an inorganic filler that has been surface-treated with a surface treatment agent. By using the inorganic filler that has been surface-treated with the surface treatment agent, it becomes easier to adjust the viscosity and Ti value of the adhesive for electronic materials to the above-mentioned ranges. In addition, by using the inorganic filler that has been surface-treated with the surface treatment agent, it is also possible to improve the moisture permeability prevention property of the cured product of the adhesive for electronic materials obtained.

[0014] Examples of the group to be introduced onto the surface of the inorganic filler by the surface treatment include alkyl groups having 1 to 20 carbon atoms, such as methyl, ethyl, propyl, butyl, hexyl, cyclohexyl, octyl, 2-ethylhexyl, lauryl, and stearyl groups, epoxy groups, such as glycidyl and 3,4-epoxycyclohexyl groups, primary, secondary, or tertiary amino groups, alkoxyl groups, vinyl groups, (meth)acryloyl groups, sulfide groups, mercapto groups, isocyanate groups, ureido groups, pyridyl groups, styryl groups, ether bonds, ester bonds, and thiol groups. Among these, epoxy groups and (meth)acryloyl groups are preferred. In this specification, the term "(meth)acryloyl" means acryloyl or methacryloyl.

[0015] The preferable lower limit of the polar term δp of the Hansen solubility parameter of the above surface treatment agent is 3.5 MPa. 0.5 , the preferred upper limit is 6.0MPa 0.5 When the Δp of the surface treatment agent is in this range, it becomes easier to adjust the viscosity and Ti value of the resulting adhesive for electronic materials to be in the above-mentioned ranges. The polarity term δp of the Hansen solubility parameter can be derived from the structural formula by calculation using HSP software, such as Hansen Solubility Parameter in Practice (HSPiP).

[0016] Specific examples of the surface treatment agent include silane coupling agents having an alkyl group such as methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, methyltrichlorosilane, butyltrichlorosilane, and trifluoropropyltrimethoxysilane; silane coupling agents having a phenyl group such as phenyltrimethoxysilane and phenyltriethoxysilane; 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,Silane coupling agents having an epoxy group, such as 4-epoxycyclohexyl)ethyltrimethoxysilane; silane coupling agents having an amino group, such as N-phenyl-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane; and vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, vinyltrichlorosilane, allyltrichlorosilane, allyltrimethoxysilane, allyltriethoxysilane, and p-styryltrimethoxysilane. Examples of the silane coupling agent include silane coupling agents having a vinyl group, silane coupling agents having a (meth)acryloyl group such as 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane, mercapto and sulfur silane coupling agents such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, and 3-octanoylthio-1-propyltriethoxysilane, ureidosilane coupling agents such as 3-ureidopropyltriethoxylane, and isocyanate silane coupling agents such as 3-isocyanatepropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane.

[0017] Examples of the method for surface treating the inorganic filler (base material particles) before surface treatment with the above-mentioned surface treatment agent include a method in which a mixture of water and the above-mentioned surface treatment agent is sprayed onto the above-mentioned base material particles in a fluidized state, and a method in which the above-mentioned base material particles are added to an organic solvent such as alcohol or toluene, and then the above-mentioned surface treatment agent and water are added, and then the water and the organic solvent are evaporated and dried using an evaporator.

[0018] The inorganic filler has a particle size D50, which is the particle size distribution where the cumulative mass from the smallest particle size side is 50%, and the lower limit is preferably 300 nm. When the D50 is 300 nm or more, the sealant has better moisture permeability prevention properties. The more preferable lower limit of the D50 is 350 nm. In addition, the inorganic filler preferably has a particle size distribution in which the particle size D50 at which the cumulative mass from the smallest particle size side is 50% is 2 μm or less, and a particle size D100 at which the cumulative mass from the smallest particle size side is 100% is 6 μm or less. When the D50 is 2 μm or less and the D100 is 6 μm or less, a sealant with excellent drawing properties is obtained. The D50 is more preferably 1 μm or less, and the D100 is more preferably 5 μm or less. The particle size distribution can be measured using a particle size distribution measuring device, such as NICOMP 380ZLS (manufactured by PARTICLE SIZING SYSTEMS).

[0019] The content of the inorganic filler is preferably 30 parts by mass relative to 100 parts by mass of the curable resin described below. When the content of the inorganic filler is 30 parts by mass or more, it becomes easier to adjust the viscosity and Ti value of the adhesive for electronic materials to the above-mentioned ranges. In addition, when the content of the inorganic filler is 30 parts by mass or more, the adhesive for electronic materials obtained also has excellent light-shielding part curing properties. From the viewpoint of drawability, the upper limit of the content of the inorganic filler is preferably 85 parts by mass, and more preferably 50 parts by mass.

[0020] The adhesive for electronic materials of the present invention preferably does not contain an organic filler having a D50 of 50 nm or more and 500 nm or less, or the content of the organic filler having a D50 of 50 nm or more and 500 nm or less is 10 parts by mass or less per 100 parts by mass of the curable resin described below. A more preferred upper limit of the content of the organic filler having a D50 of 50 nm or more and 500 nm or less is 8 parts by mass, and it is most preferred that the adhesive for electronic materials of the present invention does not contain an organic filler having a D50 of 50 nm or more and 500 nm or less.

[0021] The adhesive for electronic materials of the present invention contains a curable resin. The curable resin preferably contains at least one selected from the group consisting of epoxy compounds and (meth)acrylic compounds. By using the epoxy compound or the (meth)acrylic compound in combination with a polymerization initiator or a heat curing agent described below, the resulting adhesive for electronic materials can be made to have excellent photocurability and heat curability. In this specification, the term "(meth)acrylic" means acrylic or methacrylic.

[0022] Examples of the epoxy compound include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol E type epoxy compounds, bisphenol S type epoxy compounds, 2,2'-diallyl bisphenol A type epoxy compounds, hydrogenated bisphenol type epoxy compounds, propylene oxide-added bisphenol A type epoxy compounds, resorcinol type epoxy compounds, biphenyl type epoxy compounds, sulfide type epoxy compounds, diphenyl ether type epoxy compounds, dicyclopentadiene type epoxy compounds, naphthalene type epoxy compounds, phenol novolac type epoxy compounds, ortho-cresol novolac type epoxy compounds, dicyclopentadiene novolac type epoxy compounds, biphenyl novolac type epoxy compounds, naphthalene phenol novolac type epoxy compounds, glycidyl amine type epoxy compounds, alkyl polyol type epoxy compounds, rubber-modified epoxy compounds, and glycidyl ester compounds.

[0023] Among the above bisphenol A type epoxy compounds, commercially available ones include, for example, jER828EL, jER1004 (both manufactured by Mitsubishi Chemical Corporation), EPICLON EXA-850CRP (manufactured by DIC Corporation), and the like. Among the above bisphenol F type epoxy compounds, commercially available ones include, for example, jER806, jER4004 (both manufactured by Mitsubishi Chemical Corporation), EPICLON EXA-830CRP (manufactured by DIC Corporation), and the like. Among the above bisphenol E type epoxy compounds, a commercially available example is Epomic R710 (manufactured by Mitsui Chemicals, Inc.). Among the above bisphenol S type epoxy compounds, commercially available ones include, for example, EPICLON EXA-1514 (manufactured by DIC Corporation). Among the above 2,2'-diallylbisphenol A type epoxy compounds, a commercially available example is RE-810NM (manufactured by Nippon Kayaku Co., Ltd.). Among the above hydrogenated bisphenol type epoxy compounds, commercially available ones include, for example, EPICLON EXA-7015 (manufactured by DIC Corporation). Among the above propylene oxide-added bisphenol A type epoxy compounds, commercially available ones include, for example, EP-4000S (manufactured by ADEKA Corporation). Among the above resorcinol type epoxy compounds, a commercially available example is EX-201 (manufactured by Nagase ChemteX Corporation). Among the biphenyl type epoxy compounds, examples of commercially available compounds include jER YX-4000H (manufactured by Mitsubishi Chemical Corporation). Among the above sulfide type epoxy compounds, a commercially available example is YSLV-50TE (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Among the diphenyl ether type epoxy compounds, a commercially available example is YSLV-80DE (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Among the above dicyclopentadiene type epoxy compounds, commercially available ones include, for example, EP-4088S (manufactured by ADEKA Corporation). Among the above naphthalene type epoxy compounds, commercially available ones include, for example, EPICLON HP-4032 and EPICLON EXA-4700 (both manufactured by DIC Corporation). Among the above phenol novolac type epoxy compounds, a commercially available example is EPICLON N-770 (manufactured by DIC Corporation). Among the above ortho-cresol novolac type epoxy compounds, a commercially available example is EPICLON N-670-EXP-S (manufactured by DIC Corporation). Among the above dicyclopentadiene novolac type epoxy compounds, a commercially available example is EPICLON HP-7200 (manufactured by DIC Corporation). Among the biphenyl novolac type epoxy compounds, a commercially available example is NC-3000P (manufactured by Nippon Kayaku Co., Ltd.). Among the above naphthalenephenol novolac type epoxy compounds, a commercially available example is ESN-165S (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Among the above glycidylamine type epoxy compounds, commercially available ones include, for example, jER630 (manufactured by Mitsubishi Chemical Corporation), EPICLON430 (manufactured by DIC Corporation), TETRAD-X (manufactured by Mitsubishi Gas Chemical Company, Inc.), and the like. Commercially available examples of the alkyl polyol type epoxy compounds include ZX-1542 (manufactured by Nippon Steel Chemical & Materials Co., Ltd.), EPICLON 726 (manufactured by DIC Corporation), Epolite 80MFA (manufactured by Kyoeisha Chemical Co., Ltd.), and Denacol EX-611 (manufactured by Nagase ChemteX Corporation). Among the above rubber-modified epoxy compounds, commercially available ones include, for example, YR-450, YR-207 (both manufactured by Nippon Steel Chemical & Material Co., Ltd.), Epolead PB (manufactured by Daicel Corporation), and the like. Among the above glycidyl ester compounds, commercially available ones include, for example, Denacol EX-147 (manufactured by Nagase Chemtex Corporation). Other commercially available epoxy compounds include, for example, YDC-1312, YSLV-80XY, YSLV-90CR (all manufactured by Nippon Steel Chemical & Material Co., Ltd.), XAC4151 (manufactured by Asahi Kasei Corporation), jER1031, jER1032 (all manufactured by Mitsubishi Chemical Corporation), EXA-7120 (manufactured by DIC Corporation), and TEPIC (manufactured by Nissan Chemical Industries, Ltd.).

[0024] As the epoxy compound, a partially (meth)acrylic modified epoxy compound can also be suitably used. In this specification, the partially (meth)acrylic modified epoxy compound means a compound having one or more epoxy groups and one or more (meth)acryloyl groups in one molecule, which can be obtained by reacting a portion of the epoxy groups of an epoxy compound having two or more epoxy groups with (meth)acrylic acid.

[0025] Among the partially (meth)acrylic modified epoxy compounds, commercially available ones include, for example, UVACURE1561 and KRM8287 (both manufactured by Daicel-Allnex Corporation).

[0026] Examples of the (meth)acrylic compound include (meth)acrylic acid ester compounds, epoxy (meth)acrylates, and urethane (meth)acrylates. Among these, epoxy (meth)acrylates are preferred. In addition, the (meth)acrylic compound is preferably one having two or more (meth)acryloyl groups in one molecule from the viewpoint of reactivity. In this specification, the term "(meth)acrylate" means acrylate or methacrylate, and the term "epoxy (meth)acrylate" refers to a compound in which all epoxy groups in an epoxy compound have been reacted with (meth)acrylic acid.

[0027] Examples of the monofunctional (meth)acrylic acid ester compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, and isoctyl (meth)acrylate. Somyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, bicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2 -Butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropionate Examples of the acrylates include 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, and glycidyl (meth)acrylate.

[0028] Examples of the bifunctional (meth)acrylic acid ester compounds include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and the like. Examples of the di(meth)acrylate include butyl di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-added bisphenol A di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate, ethylene oxide-added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide-modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, and polybutadiene diol di(meth)acrylate.

[0029] In addition, examples of the (meth)acrylic acid ester compounds having three or more functional groups include trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-added isocyanuric acid tri(meth)acrylate, glycerin tri(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tris(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0030] The epoxy (meth)acrylate may, for example, be one obtained by reacting an epoxy compound with (meth)acrylic acid in the presence of a basic catalyst according to a conventional method.

[0031] As the epoxy compound serving as a raw material for synthesizing the above-mentioned epoxy (meth)acrylate, the same epoxy compounds as those mentioned above as the curable resin contained in the adhesive for electronic materials of the present invention can be used.

[0032] Among the above epoxy (meth)acrylates, commercially available ones include, for example, epoxy (meth)acrylate manufactured by Daicel-Allnex Corporation, epoxy (meth)acrylate manufactured by Shin-Nakamura Chemical Co., Ltd., epoxy (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd., and epoxy (meth)acrylate manufactured by Nagase ChemteX Corporation. Examples of the epoxy (meth)acrylates manufactured by Daicel-Allnex include EBECRYL860, EBECRYL3200, EBECRYL3201, EBECRYL3412, EBECRYL3600, EBECRYL3700, EBECRYL3701, EBECRYL3702, EBECRYL3703, EBECRYL3708, EBECRYL3800, EBECRYL6040, EBECRYL KRM7985, and EBECRYL RDX63182. Examples of the epoxy (meth)acrylates manufactured by Shin-Nakamura Chemical Co., Ltd. include EA-1010, EA-1020, EA-5323, EA-5520, EA-CHD, and EMA-1020. Examples of the epoxy (meth)acrylates manufactured by Kyoeisha Chemical Co., Ltd. include Epoxy Ester M-600A, Epoxy Ester 40EM, Epoxy Ester 70PA, Epoxy Ester 200PA, Epoxy Ester 80MFA, Epoxy Ester 3002M, Epoxy Ester 3002A, Epoxy Ester 1600A, Epoxy Ester 3000M, Epoxy Ester 3000A, Epoxy Ester 200EA, and Epoxy Ester 400EA. Examples of the epoxy (meth)acrylates manufactured by Nagase ChemteX Corporation include Denacol Acrylate DA-141, Denacol Acrylate DA-314, and Denacol Acrylate DA-911.

[0033] The urethane (meth)acrylate can be obtained, for example, by reacting an isocyanate compound with a (meth)acrylic acid derivative having a hydroxyl group in the presence of a catalytic amount of a tin compound.

[0034] Examples of the isocyanate compound that is a raw material for the urethane (meth)acrylate include isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, tolidine diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)thiophosphate, tetramethylxylylene diisocyanate, and 1,6,11-undecane triisocyanate.

[0035] As the isocyanate compound serving as a raw material for the urethane (meth)acrylate, a chain-extended isocyanate compound obtained by reacting a polyol with an excess of an isocyanate compound can also be used. Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.

[0036] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of dihydric alcohols, mono(meth)acrylates or di(meth)acrylates of trihydric alcohols, and epoxy (meth)acrylates. Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate. Examples of the dihydric alcohol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol. Examples of the trihydric alcohol include trimethylolethane, trimethylolpropane, and glycerin. The epoxy (meth)acrylate may, for example, be bisphenol A type epoxy (meth)acrylate.

[0037] Among the above urethane (meth)acrylates, commercially available ones include, for example, urethane (meth)acrylate manufactured by Toagosei Co., Ltd., urethane (meth)acrylate manufactured by Daicel-Allnex Corporation, urethane (meth)acrylate manufactured by Negami Chemical Industries Co., Ltd., urethane (meth)acrylate manufactured by Shin-Nakamura Chemical Co., Ltd., and urethane (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd. Examples of the urethane (meth)acrylates manufactured by Toagosei Co., Ltd. include M-1100, M-1200, M-1210, and M-1600. Examples of the urethane (meth)acrylates manufactured by Daicel-Allnex include EBECRYL210, EBECRYL220, EBECRYL230, EBECRYL270, EBECRYL1290, EBECRYL2220, EBECRYL4827, EBECRYL4842, EBECRYL4858, EBECRYL5129, EBECRYL6700, EBECRYL8402, EBECRYL8803, EBECRYL8804, EBECRYL8807, EBECRYL9260, and the like. Examples of the urethane (meth)acrylates manufactured by Negami Chemical Industrial Co., Ltd. include Art Resin UN-330, Art Resin SH-500B, Art Resin UN-1200TPK, Art Resin UN-1255, Art Resin UN-3320HB, Art Resin UN-7100, Art Resin UN-9000A, Art Resin UN-9000H, etc. Examples of the urethane (meth)acrylates manufactured by Shin-Nakamura Chemical Co., Ltd. include U-2HA, U-2PHA, U-3HA, U-4HA, U-6H, U-6HA, U-6LPA, U-10H, U-15HA, U-108, U-108A, U-122A, U-122P, U-324A, U-340A, U-340P, U-1084A, U-2061BA, UA-340P, UA-4000, UA-4100, UA-4200, UA-4400, UA-5201P, UA-7100, UA-7200, and UA-W2A. Examples of the urethane (meth)acrylates manufactured by Kyoeisha Chemical Co., Ltd. include AH-600, AI-600, AT-600, UA-101I, UA-101T, UA-306H, UA-306I, and UA-306T.

[0038] The ratio of (meth)acryloyl groups in the total of epoxy groups and (meth)acryloyl groups in the curable resin is preferably 30 mol % or more and 95 mol % or less. When the ratio of (meth)acryloyl groups is within this range, the adhesive for electronic materials obtained has superior adhesion, and when the adhesive for electronic materials obtained is used as a sealant for liquid crystal display elements, it has superior low liquid crystal contamination.

[0039] When the obtained adhesive for electronic materials is used as a sealant for liquid crystal display elements, the above-mentioned curable resin preferably has a hydrogen-bonding unit such as an -OH group, an -NH- group, or an -NH2 group, from the viewpoint of further suppressing contamination of the liquid crystal.

[0040] The preferred lower limit of the total content of the curable resin in 100 parts by mass of the adhesive for electronic materials of the present invention is 30 parts by mass, and the preferred upper limit is 90 parts by mass. When the total content of the curable resin is within this range, the resulting adhesive for electronic materials has better curability and adhesiveness. The more preferred lower limit of the total content of the curable resin is 50 parts by mass, and the more preferred upper limit is 80 parts by mass.

[0041] The adhesive for electronic materials of the present invention preferably contains at least one selected from the group consisting of a polymerization initiator and a heat curing agent.

[0042] Examples of the polymerization initiator include a photoradical polymerization initiator that generates radicals upon irradiation with light, and a thermal radical polymerization initiator that generates radicals upon heating.

[0043] Examples of the photoradical polymerization initiator include benzophenone-based compounds, acetophenone-based compounds, acylphosphine oxide-based compounds, titanocene-based compounds, oxime ester-based compounds, benzoin ether-based compounds, and thioxanthone-based compounds. Specific examples of the photoradical polymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholinyl)phenyl)-1-butanone, 2,2-dimethoxy-1,2-diphenylethan-1-one, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1,2-diphenylethan-1-one ... ethyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 1-(4-(2-hydroxyethoxy)-phenyl)-2-hydroxy-2-methyl-1-propan-1-one, 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyloxime), 2,4,6-trimethylbenzoyldiphenylphosphine oxide, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and the like. The above-mentioned photoradical polymerization initiators may be used alone or in combination of two or more kinds.

[0044] Examples of the thermal radical polymerization initiator include those composed of an azo compound, an organic peroxide, etc. Among them, from the viewpoint of suppressing contamination of the liquid crystal, an initiator composed of an azo compound (hereinafter also referred to as an "azo initiator") is preferable. The thermal radical polymerization initiators may be used alone or in combination of two or more kinds. Among the above azo initiators, commercially available ones include, for example, VPE-0201, VPE-0401, VPE-0601, VPS-0501, VPS-1001, V-65, and V-501 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).

[0045] Examples of the organic peroxide include ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, peroxy esters, diacyl peroxides, and peroxydicarbonates.

[0046] The content of the polymerization initiator is preferably 0.01 parts by mass at the lower limit and 10 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By setting the content of the polymerization initiator within this range, the adhesive for electronic materials obtained has better storage stability and curability. The more preferred lower limit of the content of the polymerization initiator is 0.1 parts by mass, and the more preferred upper limit is 5 parts by mass.

[0047] Examples of the heat curing agent include organic acid hydrazides, imidazole derivatives, amine compounds, polyhydric phenol compounds, acid anhydrides, etc. Among these, organic acid hydrazides are preferably used. The above heat curing agents may be used alone or in combination of two or more kinds.

[0048] Examples of the organic acid hydrazide include sebacic acid dihydrazide, isophthalic acid dihydrazide, adipic acid dihydrazide, and malonic acid dihydrazide. Among the above organic acid hydrazides, commercially available ones include, for example, organic acid hydrazides manufactured by Otsuka Chemical Co., Ltd., organic acid hydrazides manufactured by Ajinomoto Fine-Techno Co., Ltd., and organic acid hydrazides manufactured by Nippon Finechem Co., Ltd. Examples of the organic acid hydrazides available from Otsuka Chemical Co., Ltd. include SDH and ADH. Examples of the organic acid hydrazides manufactured by Ajinomoto Fine-Techno Co., Inc. include Amicure VDH, Amicure VDH-J, Amicure UDH, and Amicure UDH-J. The organic acid hydrazide manufactured by Japan Finechem Co., Ltd. is, for example, MDH.

[0049] The content of the heat curing agent is preferably 1 part by mass at the lower limit and 50 parts by mass at the upper limit relative to 100 parts by mass of the curable resin. By setting the content of the heat curing agent within this range, the adhesive for electronic materials obtained can have excellent heat curing properties without deteriorating the application property and storage stability. The more preferred upper limit of the content of the heat curing agent is 30 parts by mass.

[0050] The adhesive for electronic materials of the present invention may contain a silane coupling agent. The silane coupling agent mainly serves as an adhesion aid for providing good adhesion between the adhesive for electronic materials and a substrate or the like.

[0051] Suitable examples of the silane coupling agent include 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-isocyanatopropyltrimethoxysilane, etc. These are excellent in the effect of improving adhesion to a substrate, etc., and when the resulting adhesive for electronic materials is used as a sealant for a liquid crystal display element, it is possible to suppress outflow of the curable resin into the liquid crystal. The above silane coupling agents may be used alone or in combination of two or more kinds.

[0052] The preferred lower limit of the content of the silane coupling agent in 100 parts by mass of the adhesive for electronic materials of the present invention is 0.1 parts by mass, and the preferred upper limit is 10 parts by mass. By having the content of the silane coupling agent in this range, the effect of improving adhesion is more excellent, and when the adhesive for electronic materials obtained is used as a sealant for liquid crystal display elements, the occurrence of liquid crystal contamination can be further suppressed. The more preferred lower limit of the content of the silane coupling agent is 0.3 parts by mass, and the more preferred upper limit is 5 parts by mass.

[0053] The adhesive for electronic materials of the present invention may further contain additives such as a light-shielding agent, a stress relaxation agent, a reactive diluent, a thixotropic agent, a spacer, a curing accelerator, an antifoaming agent, a leveling agent, and a polymerization inhibitor, as necessary.

[0054] Examples of methods for producing the adhesive for electronic materials of the present invention include a method of mixing a curable resin, an inorganic filler, a polymerization initiator, a thermosetting agent, etc. using a mixer such as a Homo Disper, a Homo Mixer, a universal mixer, a planetary mixer, a kneader, or a three-roll mill.

[0055] By blending conductive fine particles with the adhesive for electronic materials of the present invention, a vertically conductive material can be produced.

[0056] The conductive fine particles may be metal balls, fine resin particles having a conductive metal layer formed on the surface thereof, etc. Among them, fine resin particles having a conductive metal layer formed on the surface thereof are preferable because the excellent elasticity of the fine resin particles allows conductive connection without damaging a transparent substrate, etc.

[0057] The adhesive for electronic materials of the present invention is suitably used as a sealant for display elements, and is particularly suitably used as a sealant for liquid crystal display elements. A liquid crystal display device containing a cured product of the adhesive for electronic materials of the present invention also constitutes the present invention.

[0058] The liquid crystal display element of the present invention is preferably a liquid crystal display element with a narrow frame design. Specifically, it is preferable that the width of the frame part surrounding the liquid crystal display part is 2 mm or less. When the liquid crystal display element of the present invention is produced, the coating width of the adhesive for electronic materials of the present invention is preferably 1 mm or less.

[0059] The adhesive for electronic materials of the present invention can be suitably used in the manufacture of a liquid crystal display element by a liquid crystal dropping method. Examples of the method for manufacturing the liquid crystal display element of the present invention by the liquid crystal dropping method include the following methods. First, a step is performed in which the adhesive for electronic materials of the present invention is applied to a substrate by screen printing, dispenser application, or the like, to form a frame-shaped seal pattern. Next, a step is performed in which minute droplets of liquid crystal are dropwise applied onto the entire surface within the frame of the seal pattern while the adhesive for electronic materials of the present invention is still in an uncured state, and another substrate is immediately superimposed. After that, a liquid crystal display element can be obtained by a step of irradiating the seal pattern portion with light such as ultraviolet light to provisionally cure the adhesive for electronic materials, and a step of heating the provisionally cured adhesive for electronic materials to fully cure it. Effect of the Invention

[0060] According to the present invention, it is possible to provide an adhesive for electronic materials that is excellent in drawability and in preventing residue on the wall of a syringe. Also, according to the present invention, it is possible to provide a liquid crystal display element using the adhesive for electronic materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0061] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0062] (Preparation of Surface-Treated Inorganic Filler A) 10 parts by mass of silica (manufactured by Nippon Shokubai Co., Ltd., "Seahoster KE-S100") was placed in a Henschel mixer, dispersed in 100 parts by mass of ethanol in which 3.5 parts by mass of 3-glycidoxypropyltrimethoxysilane had been dissolved, and the mixture was reacted under reflux of the ethanol for 1 hour. The mixture was then crushed in a ball mill to prepare epoxy-treated silica (surface-treated inorganic filler A). The particle size distribution of the obtained surface-treated inorganic filler A was measured using a particle size distribution measuring device ("NICOMP 380ZLS" manufactured by PARTICLE SIZING SYSTEMS), and the results were that D50 was 970 nm and D100 was 3.2 μm. The polar term δp of the Hansen solubility parameter of 3-glycidoxypropyltrimethoxysilane used as the surface treatment agent is 5.32 MPa. 0.5 It is.

[0063] (Preparation of Surface-Treated Inorganic Filler B) The same procedure as in "(Preparation of Surface-Treated Inorganic Filler A)" was carried out, except that 5 parts by mass of 3-aminopropyltrimethoxysilane was used instead of 3-glycidoxypropyltrimethoxysilane, to obtain amino group-treated silica (surface-treated inorganic filler B). The particle size distribution of the obtained surface-treated inorganic filler B was measured using a particle size distribution measuring device (NICOMP 380ZLS, manufactured by PARTICLE SIZING SYSTEMS), and the results were D50 was 1010 nm and D100 was 3.3 μm. The polar term δp of the Hansen solubility parameter of the 3-aminopropyltrimethoxysilane used as the surface treatment agent was 4.23 MPa. 0.5 It is.

[0064] (Preparation of Surface-Treated Inorganic Filler C) A fluoroalkyl group-treated silica (surface-treated inorganic filler C) was obtained by carrying out the same operation as in "(Preparation of surface-treated inorganic filler A)" above, except that 4 parts by mass of trifluoropropyltrimethoxysilane was used instead of 3-glycidoxypropyltrimethoxysilane. The particle size distribution of the obtained surface-treated inorganic filler C was measured using a particle size distribution measuring device (NICOMP 380ZLS, manufactured by PARTICLE SIZING SYSTEMS), and the results were D50 of 980 nm and D100 of 3.1 μm. The polar term δp of the Hansen solubility parameter of trifluoropropyltrimethoxysilane used as the surface treatment agent was 3.22 MPa. 0.5 It is.

[0065] (Examples 1 to 10, Comparative Examples 1 to 9) According to the compounding ratios shown in Tables 1 and 2, each material was stirred with a planetary mixer (Thinky Corporation, "Awatori Rentaro") and then mixed uniformly with a ceramic triple roll to obtain adhesives for electronic materials of Examples 1 to 10 and Comparative Examples 1 to 9. In the table, Acryset BPF307 is a bisphenol F type epoxy compound with acrylic rubber particles dispersed therein (acrylic rubber particle content: 19 to 21% by mass).

[0066] (Viscosity and Thixotropic Index) The viscosity of each of the obtained adhesives for electronic materials was measured using an E-type viscometer (manufactured by BROOK FIELD Corp., "DV-III") at 25° C. and 0.01 rpm. Furthermore, for each of the obtained adhesives for electronic materials, the viscosity was measured using an E-type viscometer (manufactured by Brook Field, "DV-III") at 25°C and 0.01 rpm, and divided by the viscosity measured at 25°C and 1 rpm to calculate the thixotropic index. The results are shown in Tables 1 and 2.

[0067] <Evaluation> The adhesives for electronic materials obtained were evaluated as follows, and the results are shown in Tables 1 and 2.

[0068] (Prevents residue on the wall of the syringe) 10 g of each of the obtained electronic material adhesives was filled into a syringe (Musashi Engineering Co., Ltd., "PSY-10EU-OR") and a 0.4 mmΦ nozzle was attached. Then, the electronic material adhesive was discharged at a pressure of 100 to 400 kPa using a tabletop applicator (Musashi Engineering Co., Ltd., "SHOTMASTER 300") and an air pulse type dispenser (Musashi Engineering Co., Ltd., "ML-808EX"), and nine frame-shaped seal patterns of 3.5 cm x 3.5 cm were drawn on a 15 cm x 15 cm glass substrate. Next, 6 μL of liquid crystal was dropped into the frame of each seal pattern, and the substrates were bonded together by vacuum pressure bonding to prepare cells. This was repeated until liquid crystal leakage occurred in all cells, at which point the preparation of the cells was terminated, and the electronic material adhesive remaining in the syringe was weighed. The prevention of adhesive remaining on the wall of the syringe was evaluated as follows: if less than 3 g of adhesive for electronic materials remained in the syringe, it was marked as "○", if 3 g or more but less than 5 g was marked as "△", and if 5 g or more was marked as "×".

[0069] (Drawability) In 100 parts by mass of each of the obtained electronic material adhesives, 1 part by mass of spacer particles (manufactured by Sekisui Chemical Co., Ltd., "Micropearl SP-2050") having an average particle size of 5 μm was uniformly dispersed using a planetary stirrer. Next, the electronic material adhesive with the spacer particles dispersed therein was filled into a syringe (manufactured by Musashi Engineering Co., Ltd., "PSY-10EU-OR") and subjected to a degassing treatment, after which the electronic material adhesive was applied to one of two transparent substrates using a dispenser (manufactured by Musashi Engineering Co., Ltd., "SHOTMASTER300") so as to draw a frame-shaped seal pattern. Thereafter, the other transparent substrate was bonded under a reduced pressure of 5 Pa using a vacuum bonding device to obtain a cell. The obtained cell was then exposed to 100 mW / cm using a metal halide lamp. 2After being irradiated with ultraviolet light (wavelength 365 nm) for 30 seconds, the electronic material adhesive was cured by heating at 120°C for 1 hour to obtain a test piece. The electronic material adhesive in the obtained test piece was observed, and the drawability was evaluated as follows: if there were no disconnections or undulations in the seal pattern and clean lines were drawn, it was marked "○", if there were no disconnections but the electronic material adhesive had slight undulations, it was marked "△", and if there were disconnections, it was marked "×".

[0070] (Anti-insertion properties) In 100 parts by mass of each of the obtained electronic material adhesives, 1 part by mass of spacer particles (manufactured by Sekisui Chemical Co., Ltd., "Micropearl SP-2050") with an average particle size of 5 μm was uniformly dispersed by a planetary stirring device. Next, the electronic material adhesive with the spacer particles dispersed therein was filled into a syringe (manufactured by Musashi Engineering Co., Ltd., "PSY-10EU-OR"), and after degassing treatment, the electronic material adhesive was applied to one of the two transparent substrates using a dispenser (manufactured by Musashi Engineering Co., Ltd., "SHOTMASTER300") so as to draw a frame-shaped seal pattern. Next, minute droplets of liquid crystal (manufactured by Chisso Corporation, "JC-5004LA") were dropwise applied to the entire surface within the frame of the seal pattern, and the other transparent substrate was immediately bonded. After that, a metal halide lamp was used to illuminate the seal pattern portion at 100 mW / cm. 2 After being irradiated with ultraviolet light (wavelength 365 nm) for 30 seconds, the film was heated at 120° C. for 1 hour to obtain a liquid crystal display device. The shape of the seal pattern of the obtained liquid crystal element was observed. As a result, the resistance to insertion was evaluated as follows: "○" for the seal pattern shape not disturbed by the internal liquid crystal, "△" for the seal pattern shape disturbed, and "×" for the liquid crystal breaking through the seal pattern and leaking out.

[0071] (Light-shielding part curability) Substrate A was prepared by depositing chrome on half of one side of 0.7 mm thick Corning glass, and substrate B was prepared by depositing chrome on the entire one side. Next, 1 part by mass of spacer particles (Micropearl SP-2050, manufactured by Sekisui Chemical Co., Ltd.) with an average particle size of 5 μm was uniformly dispersed in 100 parts by mass of each electronic material adhesive using a planetary stirrer. The electronic material adhesive with the spacer particles dispersed therein was then applied to the center of substrate A (the boundary between the chrome-deposited and non-deposited portions), and substrate B was then attached, after which the electronic material adhesive was thoroughly crushed, and a metal halide lamp was used from the substrate A side to illuminate the electronic material at 100 mW / cm. 2 The sample was exposed to ultraviolet light (wavelength 365 nm) for 30 seconds. Thereafter, the substrates A and B were peeled off using a cutter, and the spectrum of the adhesive for electronic materials at a point 50 μm away from the edge of the direct ultraviolet irradiation part (part that was shielded by chrome deposition) was measured by a microscopic IR method, and the conversion rate of the (meth)acryloyl group in the adhesive for electronic materials was obtained by the following method. That is, the peak area of ​​815 to 800 cm-1 was taken as the peak area of ​​the (meth)acryloyl group, and the peak area of ​​845 to 820 cm-1 was taken as the reference peak area, and the conversion rate of the (meth)acryloyl group was calculated by the following formula. The curability of the shielded part was evaluated by giving a conversion rate of the (meth)acryloyl group of 70% or more as "◎", a conversion rate of 60% or more but less than 70% as "○", a conversion rate of 50% or more but less than 60% as "△", and a conversion rate of less than 50% as "×". Conversion rate of (meth)acryloyl group=(1-(peak area of ​​(meth)acryloyl group after UV irradiation / reference peak area after UV irradiation) / (peak area of ​​(meth)acryloyl group before UV irradiation / reference peak area before UV irradiation))×100

[0072] (Moisture permeability prevention) Each of the obtained adhesives for electronic materials was applied to a smooth release film using a coater to a thickness of 200 to 300 μm. Then, a metal halide lamp was used to apply the adhesive to the film at a light intensity of 100 mW / cm. 2After being irradiated with ultraviolet light (wavelength 365 nm) for 30 seconds, the adhesive for electronic materials was cured by heating at 120°C for 1 hour to obtain a film for moisture permeability measurement. A cup for the moisture permeability test was prepared according to the method for testing moisture permeability of moisture-proof packaging materials (cup method) of JIS Z 0208, and the obtained film for moisture permeability measurement was attached to the cup. The cup was then placed in a constant temperature and humidity oven at 80°C and 90% RH to measure the moisture permeability. When the obtained moisture permeability value was 70 g / m 2 - 24hr or less is marked as "◎", 70g / m 2 Over 100g / m2 for 24hr 2 - 24 hours or less is marked as "○", 100g / m 2 Over 130g / m2 for 24hr 2 - 24hr or less is marked as "△", 130g / m 2 When the test time exceeded 24 hours, the moisture permeability was evaluated as "×".

[0073] [Table 1]

[0074] [Table 2] [Industrial Applicability]

[0075] According to the present invention, it is possible to provide an adhesive for electronic materials that is excellent in drawability and in preventing residue on the wall of a syringe. Also, according to the present invention, it is possible to provide a liquid crystal display element using the adhesive for electronic materials.

Claims

1. An adhesive for electronic materials containing a curable resin and an inorganic filler, The viscosity measured using an E-type viscometer at 25°C and 0.01 rpm is 1.5 million mPa·s or less, and The thixotropic index, which is the value obtained by dividing the viscosity measured using an E-type viscometer at 25°C and 0.01 rpm by the viscosity measured at 25°C and 1 rpm, is 3.0 or more and 5.0 or less.

1. An adhesive for electronic materials comprising:

2. 2. The adhesive for electronic materials according to claim 1, wherein a content of the inorganic filler is 30 parts by mass or more based on 100 parts by mass of the curable resin.

3. The inorganic filler includes an inorganic filler that has been surface-treated with a surface treatment agent, The surface treatment agent has a polarity term δp of the Hansen solubility parameter of 3.5 MPa. 0.5 More than 6.0 MPa 0.5 The adhesive for electronic materials according to claim 1 or 2, wherein:

4. 3. The adhesive for electronic materials according to claim 1, wherein the inorganic filler has a particle size D50, at which a cumulative mass from the smallest particle size side accounts for 50% in a particle size distribution, of 300 nm or more.

5. 3. The adhesive for electronic materials according to claim 1 or 2, wherein the inorganic filler has, in a particle size distribution, a particle size D50 at which an integrated mass from the minimum particle size side accounts for 50% of the total mass, being 2 μm or less, and a particle size D100 at which an integrated mass from the minimum particle size side accounts for 100% of the total mass, being 6 μm or less.

6. 3. The adhesive for electronic materials according to claim 1 or 2, which does not contain any organic filler having a particle size D50, which is 50% of the cumulative mass from the smallest particle size side in the particle size distribution, of 50 nm or more and 500 nm or less, or the content of organic filler having D50 of 50 nm or more and 500 nm or less is 10 parts by mass or less per 100 parts by mass of the curable resin.

7. A liquid crystal display device comprising a cured product of the adhesive for electronic materials according to claim 1 or 2.

Citation Information

Patent Citations

  • Sealing agent for dropping process of LCD panel

    JP2001133794A

  • Curing resin composition and sealants and end-sealing materials for displays

    WO2002092718A1